Human monkeypox virus infection in women and non-binary individuals during the 2022 outbreaks: a global case series. Issue 10367 (3rd December 2022) - Thornhill, John P; Palich, Romain; Ghosn, Jade; Walmsley, Sharon; Moschese, Davide; Cortes, Claudia P; Galliez, Rafael Mello; Garlin, Amy B; Nozza, Silvia; Mitja, Oriol; Radix, Asa E; Blanco, Jose Luis; et al.
Summary: Background: Between May and November, 2022, global outbreaks of human monkeypox virus infection have been reported in more than 78 000 people worldwide, predominantly in men who have sex with men. We describe the epidemiological and clinical characteristics of monkeypox virus infection in cisgender (cis) and transgender (trans) women and non-binary individuals assigned female sex at birth to improve identification and understanding of risk factors. Methods: International collaborators in geographical locations with high numbers of diagnoses of monkeypox virus infection were approached and invited to contribute data on women and non-binary individuals with confirmed monkeypox virus infection. Contributing centres completed deidentified structured case-report spreadsheets, adapted and developed by participating clinicians, to include variables of interest relevant to women and non-binary individuals assigned female at birth. We describe the epidemiology and clinical course observed in the reported infections. Findings: Collaborators reported data for a total of 136 individuals with monkeypox virus infection who presented between May 11 and Oct 4, 2022, across 15 countries. Overall median age was 34 years (IQR 28–40; range 19–84). The cohort comprised 62 trans women, 69 cis women, and five non-binary individuals (who were, because of small numbers, grouped with cis women to form a category of people assigned female at birth for the purpose of comparison). 121 (89%) of 136 individuals reported sex with men. 37 (27%) of all individuals were living with HIV, with a higher proportion among trans women (31 [50%] of 62) than among cis women and non-binary individuals (six [8%] of 74). Sexual transmission was suspected in 55 (89%) trans women (with the remainder having an unknown route of transmission) and 45 (61%) cis women and non-binary individuals; non-sexual routes of transmission (including household and occupational exposures) were reported only in cis women and non-binary individuals. 25 (34%) of 74 cis women and non-binary individuals submitted to the case series were initially misdiagnosed. Overall, among individuals with available data, rash was described in 124 (93%) of 134 individuals and described as anogenital in 95 (74%) of 129 and as vesiculopustular in 105 (87%) of 121. Median number of lesions was ten (IQR 5-24; range 1–200). Mucosal lesions involving the vagina, anus, or oropharynx or eye occurred in 65 (55%) of 119 individuals with available data. Vaginal and anal sex were associated with lesions at those sites. Monkeypox virus DNA was detected by PCR from vaginal swab samples in all 14 samples tested. 17 (13%) individuals were hospitalised, predominantly for bacterial superinfection of lesions and pain management. 33 (24%) individuals were treated with tecovirimat and six (4%) received post-exposure vaccinations. No deaths were reported. Interpretation: The clinical features of monkeypox in women and non-binary individuals were similar to those described in men, including the presence of anal and genital lesions with prominent mucosal involvement. Anatomically, anogenital lesions were reflective of sexual practices: vulvovaginal lesions predominated in cis women and non-binary individuals and anorectal features predominated in trans women. The prevalence of HIV co-infection in the cohort was high. Funding: None.